HUBUNGAN PERSEPSI TENTANG DAMPAK PORNOGRAFI DENGAN PERILAKU MENGAKSES SITUS PORNOGRAFI PADA REMAJA - Agil, Hilda Meriyandah; Maulidia, Yulif; Indrawati, Lina (Jurnal Ayurveda Medistra, 2022)
Background: Internet media is a very accessible medium to access pornographic sites. The behavior of teenagers accessing pornographic sites is a fairly high case at this time. This behavior is influenced by several factors of encouragement both from outside and from within the teenager himself. One of the motivating factors from within the youth itself is the perception of the youth themselves. Perceptions about the impact of pornography are teenagers' perspectives on matters related to the dangers of pornography Objective: To determine the characteristics of adolescents based on age, age and use of the internet, as well as to determine the relationship between perceptions about the impact of pornography and the behavior of accessing pornographic sites on adolescents in RW.02, PErumahan Green Garden Rorotan. Method: This study uses a correlational study with a cross-sectional approach aimed at analyzing the relationship between perceptions of the impact of pornography and the behavior of accessing pornographic sites on adolescents in RW.02 of the Rorotan Green Garden Housing which was selected proportionally. The population of this study were all teenagers in RW.02 Green Garden Rorotan Housing with a total of 102 teenagers. The sampling technique in this study used proportional stratified random sampling, so that the sample amounted to 89 teenagers. Result: The research data was obtained using a Likert scale. The results of the study of 89 respondents (100%) showed that 23 respondents (25.8%) had negative perceptions of accessing pornographic sites and 2 respondents (2.2%) with behavior accessing pornographic sites. While respondents who have a positive perception of the behavior of accessing porn sites in the high category are 38 respondents (42.7%) and those with the behavior of accessing porn sites in the low category are 26 respondents (29.2%). Conclusion: Analysis of the chi-square correlation test obtained the -value of 0.003 (0.05), so it can be concluded that H1 is accepted, which means that there is a significant relationship between perceptions of the impact of pornography and the behavior of accessing pornographic sites on adolescents. Teenagers are expected to better understand the dangers of pornography and be able to control themselves in internet access, and avoid pornographic sites.